Teori-Teori Belajar dalam Pembelajaran - Putriani Lubis; Maria Bintang Hasibuan; Gusmaneli Gusmaneli (STIKes Ibnu Sina Ajibarang, 2024)
The aim of the research is to help teachers and educators understand how students learn and how to increase the effectiveness of the learning process. By understanding learning theories, teachers and educators can develop effective learning strategies and improve the quality of education. In synthesis, learning theories play an important role in understanding how students process information and how teachers can improve learning effectiveness. Teachers can use various strategies and techniques based on learning theories to improve the quality of learning and student learning outcomes.